2008
DOI: 10.1111/j.1741-4520.2008.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital malformations in Cross River and Akwa Ibom states of Nigeria from 1980–2003

Abstract: A retrospective study was conducted on the prevalence of congenital malformations in Cross River and Akwa Ibom states of Nigeria from 1980-2003. These states lie in the South-South geopolitical zone of Nigeria. The aim of the study was to determine the percentage of occurrence of birth defects and provide reference data for this part of the country. Details of congenital malformations were compiled by reviewing the delivery register of the records departments of maternity sections of University of Calabar Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
37
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 11 publications
12
37
1
Order By: Relevance
“…Our prevalence rate is lower than those reported in many other population based studies in published literature which varies between 100 and 300 per 10,000 births [5, 23, 24, 33]. However, this difference is most likely due to the difference in the study design and our study compares well with the prevalence rate of congenital malformations from some other similarly designed population based studies using ICD10 classification that have reported similarly lower prevalence rates of less than 100 per 10, 000 births [3, 9, 32, 34]. It is interesting to note that the only other population based study from the Caribbean is from Cuba and has reported similarly low prevalence of congenital malformation at 47/10,000 live births [2].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our prevalence rate is lower than those reported in many other population based studies in published literature which varies between 100 and 300 per 10,000 births [5, 23, 24, 33]. However, this difference is most likely due to the difference in the study design and our study compares well with the prevalence rate of congenital malformations from some other similarly designed population based studies using ICD10 classification that have reported similarly lower prevalence rates of less than 100 per 10, 000 births [3, 9, 32, 34]. It is interesting to note that the only other population based study from the Caribbean is from Cuba and has reported similarly low prevalence of congenital malformation at 47/10,000 live births [2].…”
Section: Discussionsupporting
confidence: 60%
“…This was followed by malformations of the musculoskeletal system (16% of all malformations) and digestive system (13% of all malformations). Once again, it is evident from the literature that there are large reported variations in pattern of congenital malformations involving different body systems in different populations around the world [39, 14–16]. A similar study from Saudi Arabia reported that the major congenital anomalies among all live births were mostly observed in the cardiovascular system (CVS), followed by musculoskeletal/limb [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of congenital abnormalities in Europe in 2012 was 25 per 1,000 births 5. The figure included 15,867 women who had babies with congenital abnormalities at birth, 364 women who had intrauterine fetal death due to abnormalities, and 3,660 women who had termination of pregnancy for fetal abnormalities, giving a total of 19,891 in 30 countries.…”
Section: Discussionmentioning
confidence: 99%
“…The data are mainly hospital-based without taking into consideration the general population. For instance, the prevalence of congenital malformations noted in Akwa Ibom and Cross River states in the South-South region and Kano state in the North-East region of Nigeria were 0.4% and 5.8%, respectively 5,6. The figures for the South East and the South West were 0.42% and 1.58%, respectively 7,8…”
Section: Introductionmentioning
confidence: 95%